Worldview Islam dan Kapitalisme Barat - Hamid Fahmy Zarkasyi (TSAQAFAH, 2013)
In the era when the idea of similarity, equality and pluralism are disseminated in diversified area, one might face difficulty to distinguish one civilization from the other.Now capitalism is the most dominant system of economic in the world and even developed into a civilization that has a worldveiw. Capitalism also used to be claimed and accepted as universal system that could be applied to the whole world. In response to this state of mind, it is imperative that capitalism be studied and identified from its very basic concept, i.e worldview perspective, and then compared it with Islam. This paper is a preliminary attempt to identify capitalist worldview and prove that it differs fundamentally from the worldview of Islam. The capitalist vision on religion, world, life style, justice, freedom of thought, wealth, economic activities which are influenced by Western worldview is diametrically different from Islamic worldview. Based on this study it must be very clear that Muslim intellectual who intend to borrow certain concept of capitalism for the development of Islamic economic should realize there are fundamental principles of capitalism that are irreconciliable with that of Islamic economic.